L’esthétique environnementale comme cadre de pensée pour appréhender la « sensibilité paysagère » : perspectives historiques et débats contemporains - Diane Linder (VertigO)
What is the aesthetic value of a landscape, and what is at stake when one ascribes such a value to it? Environmental Aesthetics, deriving both from aesthetics and Anglo-Saxon environmentalism, points these questions. The reason why this approach is called Environmental Aesthetics rather than Aesthetics of the landscape, does not mean this approach focuses (solely) on "what environs" or on the ecological dimension of the landscape. It aims rather to establish a divergence from the picturesque in the 19th century. Therefore, whereas aesthetic sensibility is a historical foundation for environmental attitude (Hargrove, on 1979), Environmental Aesthetics clarifies its justification ground.